Da racialização a etnicização : a construção de um complexo posicionar-se - Flor, Cauê Gomes (2015)
Since 2004 the city of Lins (São Paulo) receives proportionately the largest flow of African students in São Paulo. Early in our research had about 140 students from the Portuguese Speaking Countries (PALOP): Angola, Cape Verde, Sao Tome & Principe, Mozambique and Guinea Bissau. There they live and study at the University Center of Lins (Unilins). However, are overweight young people from Angola, about 120, are the only ones who are enunciated as Angolan community. By stating this discourse, African students tout and negotiate a set of representations, state differences and promote identification processes. Thus, this work aims specifically foregrounding the experiences of these young Angolan students in Brazilian society. That there is an ethnic character positioning played by students is, and this is the hypothesis of this study, enrolled assignment expression of blackness, historical and daily to people of African descent in their collective experience. In other words, students in their stay in Brazil undergo a process of racialization. And, in response to this denial produced by a process ethnization a positioning. Which in turn articulates intersected way these two sociological divisions (race and ethnicity). Thus, as important as the intersection and articulation of these two divisions, the form, the process, the "how" students perform this agency and negotiation is critical. You know how, in what way these students are building through complex cultural processes of identity and difference figures. From this derives the following specific objectives, though no less important: i) how and why Brazil is presented as a destination for these students? ii.) As the Angolan students perceive themselves in front of the Brazilian social formation? For if on the one hand, the particulars used to identify contribute to better understand their narratives about tensions and difficulties they experience in this new socio-cultural context; on the other, the choice of Brazil as a privileged destination for these young people is closely linked to the relations that Brazil has with Angola and other countries of Palop.